Production and Marketing of Organic Vegetables on a CV. Rahayu in Sidera Village, Sigi Biromaru District, Sigi Regency - Endah Wahyunuing Asih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Organic vegetable production in Indonesia is experiencing rapid development. The global market demands organic products to meet safety for consumption, have high nutrition, and are environmentally friendly. Various kinds of organic vegetables are widely cultivated, especially in tropical climates. What factors affect the production of organic vegetables, and how is the marketing margin of organic vegetables between CV. Rahayu and Carrefour Based on the description of the discussion above, it can be concluded that: The factors of organic vegetable production include: labor, use of fertilizers, use of pesticides, use of seeds and irrigation costs, and marketing of organic vegetable CV. Rahayu is marketed to the modern market, with an average marketing margin of 19.43% or an average of Rp. 1,070.